2007
DOI: 10.1021/bi6025648
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Region between the Heptad Repeats of Paramyxovirus Fusion Proteins Is Critical for Proper F Protein Folding

Abstract: Paramyxoviruses are a diverse family which utilizes a fusion (F) protein to enter cells via fusion of the viral lipid bilayer with a target cell membrane. Although certain regions of F are known to play critical roles in membrane fusion, the function of much of the protein remains unclear. Sequence alignment of a set of paramyxovirus F proteins and analysis utilizing Block Maker identified a region of conserved amino acid sequence in a large domain between the heptad repeats of F 1 , designated CBF 1 . We empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…Previous research in multiple laboratories has indicated a role for HRA in folding and fusion (47,49,56). We have recently demonstrated that there is a role for CBF 1 in F protein folding and homotrimerization (15). Two previous studies of paramyxovirus F proteins have included mutations of a small number of residues that fall within CBF 2.…”
mentioning
confidence: 98%
“…Previous research in multiple laboratories has indicated a role for HRA in folding and fusion (47,49,56). We have recently demonstrated that there is a role for CBF 1 in F protein folding and homotrimerization (15). Two previous studies of paramyxovirus F proteins have included mutations of a small number of residues that fall within CBF 2.…”
mentioning
confidence: 98%
“…Thus, slow folding kinetics for Hendra virus G may explain the delayed appearance of an endo H-resistant population. Unlike Hendra virus F, which folds as a trimer (13,14), Hendra virus G is a tetramer composed of two disulfidelinked dimers (7). To examine folding kinetics, cross-linking analysis (13) was performed at various time points post-metabolic labeling.…”
mentioning
confidence: 99%
“…(C) Biotinylation analyses of Vero cells expressing both Hendra virus F and Hendra virus G-⌬32 were performed as described previously. (14). (B) Vero cells expressing Hendra virus G-⌬32 were labeled for 30 min and chased for the indicated times, and cross-linking analysis with DTSSP was performed as described previously (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides two heptad repeat regions (HRA and HRB) in the F 1 ectodomain, which are well known to play critical roles in paramyxovirus membrane fusion (2,11,30,39), other regions are only poorly characterized for their specific function in the fusion process itself. Interestingly, recently it has been demonstrated that a conserved region, located between both heptad repeats (HRA and HRB) of SV5 and Hendra virus F proteins, was important for regulating F protein expression and activity (13). In addition, single mutations in the globular head and outside both HR domains of SV5 and Newcastle disease virus (NDV) have been shown to allow the F protein to activate the fusion process in the absence of the receptor-binding protein (HN) (20,29).…”
mentioning
confidence: 99%